Synthesis and Characterization of Borosilicate Glass Powder-Reinforced Novel Lightweight Aluminum Matrix Composites. (22nd October 2022) - Bhowmik, Abhijit; Meher, Arabinda; Biswas, Srijit; Dey, Dipankar; Kumar, M. Saravana; Biswas, Ajay; Alsharabi, Rim M.
Abstract : Due to greater specific strength and stiffness than monolithic metal, aluminum matrix composite is in high demand. The present study investigated the interaction of borosilicate glass powder with the AA7075 aluminum alloy matrix. The lower density of borosilicate glass powder compared to AA7075 alloy makes the composite more appropriate for various industrial applications due to the increased material strength. This study uses the stir casting fabrication process to develop microsized borosilicate glass powder-reinforced aluminum matrix composites. The microstructure shows that borosilicate glass powder is near-uniformly distributed throughout the aluminum matrix. It is observed that the 9 wt (%) borosilicate glass powder-reinforced aluminum matrix composite increases the tensile strength by 40.71%, hardness by 21.21%, and impact strength by 34.37% compared to unreinforced aluminum AA7075 alloy. Pin-on-disc wear testing setup was used to determine the wear performance of the base AA7075 alloy and cast composites. The dry sliding wear test revealed that the glass powder-reinforced composites have better wear resistance properties compared to the unreinforced matrix due to the hard and rigid behavior of borosilicate glass reinforcement.